Synchronní kolorektální karcinom a nehodgkinský lymfom - popis dvou případů - Hrudka, J; Eis, V; Lisý, P; Gürlich, R; Mandys, V (Rozhledy v chirurgii, 2016)
UNLABELLED: Colorectal carcinoma represents an important cause of morbidity and mortality in adults, and its incidence in the Czech Republic is one of the world´s highest. The basic therapeutic approach is surgery: surgical removal of the affected part of the bowel together with regional lymph nodes dissection. The lymph nodes are routinely examined by means of histopathology. In this paper, we present two patients whose histological examination of mesocolic lymph nodes revealed an infiltration by synchronous malignant B-non-Hodgkin-lymphoma. Mantle cell lymphoma was present in the first case, and small cell lymphoma CLL/SLL in the other. Relevant literature is reviewed. KEY WORDS: synchronous - malignancy - colorectal - lymphoma - lymph node.
Keywords: mnohočetné primární nádory; kolorektální nádory; Česká republika; Colorectal Neoplasms; mužské pohlaví; adenokarcinom; Lymph Nodes; Adult; Czech Republic; Lymphoma, Mantle-Cell; chronická lymfatická leukemie; ženské pohlaví; Lymph Node Excision; Neoplasms, Multiple Primary; Humans; Leukemia, Lymphocytic, Chronic, B-Cell; lymfadenektomie; lymfatické uzliny; dospělí; Female; Adenocarcinoma; lidé; Male; lymfom z plášťových buněk